Anxiety and Avoidance in Attachment as Predictors of Emotional Regulation Difficulties in University Students - Jessica Morales-Sanhueza; Guadalupe Martín-Mora-Parra (Psychiatry International)
The high prevalence of anxiety and depressive symptoms in youngsters has resulted in two thirds of mental health problems emerging before the age of 25. In this context, various studies have indicated that attachment styles and emotional regulation are relevant factors for the health of this population. Likewise, a close relationship has been established between both constructs, associating secure attachment with greater regulatory skills and a lower risk of mental health problems. However, in Chile there are no studies that specifically analyze the influence of anxiety and attachment avoidance on emotional regulation, nor the influence of other factors such as biological sex. Therefore, the main purpose of this research was to analyze how these variables interact with each other. For this purpose, the Experience in Close Relationships Scale (ECR-R) and the Difficulties in Emotional Regulation Scale (DERS-E) were applied to a sample of 557 Chilean university students. The analysis of results, based on the construction of a moderated mediation model, revealed that anxiety and avoidance are predictors of emotional regulation difficulties. However, the influence of anxiety on emotional regulation would be greater than that of avoidance and would be moderated by biological sex, showing the need to design differentiated interventions for men and women.